PEMBERDAYAAN MANAJEMEN PENDIDIKAN BERBASIS MASARAKAT - Murjani Murjani (CV. ADIBA AISHA AMIRA, 2021)
Community-based education is starting to fade as we feel at this time living in religion but feels empty because some of the people live hidonesm and abandon their religious orders, customs and culture as a cultured society.